Production of Pachira glabra seed cake (Kulikuli): nutrient and sensory evaluations - Muibat Bello; Mujeeb Oladepo; Rafat Arotayo; Asiata Ibrahim; Adijat Ogundola; Adebola Akintola (Croatian Journal of Food Science and Technology)
Utilization of lesser-known food plants through value added processing is a way to develop more sustainable and healthy diets. Pachira glabra seed (Malabar chestnut) was processed into snack (Kuli-kuli) and evaluated for nutrient content and acceptability using standard methods. Proximate composition revealed that P. glabra seed and its seed cake contain 15.75% and 17.50% crude protein and 32.75% and 38.50% carbohydrate, respectively. Mineral constituent of the seed and its seed cake revealed potassium (K) 58.32 mg/kg and 53.01 mg/kg, calcium (Ca) 8.3 mg/kg and 16.9 mg/kg, magnesium (Mg) 10.2 mg/kg and 11.07 mg/kg, respectively. Sensory score shows that P. glabra seed cake was acceptable (p<0.05) in terms of flavour, taste and crispness, compared with groundnut seed cake. The study showed that the seed cake was rich in nutrients. Also, processing P. glabra into a value-added product will prevent the waste of natural resources and increase food availability for humans.